'A strange, though native coast': imperial and mercantile reactions to coastal arrival in early modern literature - Humphries, W (2019)
This thesis explores imperial and mercantile reactions to moments of coastal arrival in early modern English literature. It demonstrates the various ways in which authors presented arrival on shorelines in order to consider political, ethical, and literary issues. Coastal arrival is shown to have become particularly significant during the period, owing to England’s complicated sense of itself as an island nation with uncertain colonial aspirations. However, the thesis also reveals the connectedness between such novel representations of arrival shores and earlier classical models of literary coastal arrival. Chapter One examines competing visions of New World colonialism in the writings of Richard Hakluyt. Chapter Two traces the evolving political and ethical treatment of the shoreline in Edmund Spenser’s The Faerie Queene. Chapter Three considers allusion to and adaptation of the classical story of Aeneas’ arrival on the shores of Carthage in early modern drama. Finally, Chapter Four charts the ways in which the aspirations of seventeenth-century merchant-adventurers arriving on the shores of America were satirised on London’s stage and page. Much as the shoreline is a liminal meeting point between land and sea, so too the literature of the period explores the complex blurring of binaries that takes place at moments of coastal arrival.